2020
DOI: 10.1136/bjophthalmol-2020-317768
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment and perceptual visual disorders in children with cerebral palsy in Nigeria

Abstract: Cerebral palsy (CP) is the most common cause of childhood physical disability globally. This study describes the spectrum of ocular morbidity and visual impairment in a community-based (recruited by key informants) sample of children with CP in Cross River State, Nigeria.MethodsA paediatric neurologist clinically confirmed CP and assessed systemic comorbidity. Ophthalmological assessment included developmental age appropriate acuity tests, objective refraction and objective and subjective tests of perceptual v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…These investigations have shown that children with CP commonly have difficulties in visuo-perceptual, visuo-spatial and visuo-constructive activities, regardless of their level of visual acuity (West et al, 2021). The severity and patterns of the deficits closely correlate with the extent and distribution of reduction of white matter as well as impairment of the dorsal stream pathway, interfering with attentional, spatial and motor aspects of visual cognition as well as with global visual processing (Fazzi et al, 2004;Duke et al, 2020). MRI tractography has shown that when the inferior longitudinal fasciculi in periventricular temporal lobe white matter are affected, the ventral stream dysfunctions alter detailed visual processing and in this way, visual recognition (Ortibus et al, 2012), and when the superior longitudinal fasciculi are affected, the resulting dorsal stream dysfunctions impair visual mapping of the visual scene, leading to simultanagnostic vision limiting visual search, with lack of accuracy of visual guidance of movement (optic ataxia) (Bauer et al, 2014) (see below for a detailed description).…”
Section: Optical Ophthalmological and Neurological Disorders Associated With Cortical Or Cerebral Visual Impairmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These investigations have shown that children with CP commonly have difficulties in visuo-perceptual, visuo-spatial and visuo-constructive activities, regardless of their level of visual acuity (West et al, 2021). The severity and patterns of the deficits closely correlate with the extent and distribution of reduction of white matter as well as impairment of the dorsal stream pathway, interfering with attentional, spatial and motor aspects of visual cognition as well as with global visual processing (Fazzi et al, 2004;Duke et al, 2020). MRI tractography has shown that when the inferior longitudinal fasciculi in periventricular temporal lobe white matter are affected, the ventral stream dysfunctions alter detailed visual processing and in this way, visual recognition (Ortibus et al, 2012), and when the superior longitudinal fasciculi are affected, the resulting dorsal stream dysfunctions impair visual mapping of the visual scene, leading to simultanagnostic vision limiting visual search, with lack of accuracy of visual guidance of movement (optic ataxia) (Bauer et al, 2014) (see below for a detailed description).…”
Section: Optical Ophthalmological and Neurological Disorders Associated With Cortical Or Cerebral Visual Impairmentmentioning
confidence: 99%
“…Some children with CVI show academic success similar to their typical peers, while others show significant learning disabilities. Early brain damage is commonly diffuse, so tends to affect multiple brain functions, leading to associated neurological disorders including epilepsy, intellectual disability and CP, which can compound the deleterious effects of CVI on development ( Lowery et al, 2006 ; Duke et al, 2020 ). Several studies have been conducted in children with CP to identify and characterize their associated CVI ( Stiers et al, 2002 ; Fazzi et al, 2004 ; Pehere et al, 2018 ).…”
Section: The Differences Between Typical Vision and Cortical Or Cerebral Visual Impairmentmentioning
confidence: 99%
“…It is possible that a questionnaire approach is not the best one for this population. Separate from how the IQI performed we did find evidence of under recognition/reporting of visual morbidity by the carers of these children (Duke et al, 2020). In retrospect it could be argued that we should have screened for CVI or PVD before recruiting e.g., perhaps had a cut off requiring a certain number of positive IQI responses to be eligible for recruitment.…”
Section: Discussionmentioning
confidence: 82%
“…It was previously shown in India, Bangladesh and more recently in the United Kingdom ( Mitry et al, 2016 ; Philip et al, 2016 ; Tsirka et al, 2020 ), that this latter group of symptoms of higher visual processing problems or PVD are commonly present in children with CP; we have previously published a detailed visual assessment of the children recruited for this trial showing high rates of visual pathology (including 46% PVD measured objectively and 49% CVI, dropping to 16% if optic atrophy excluded) ( Duke et al, 2020 ).…”
Section: Introductionmentioning
confidence: 95%
“…In the second stage, children had a comprehensive history taken and detailed examination, including neurological examination and confirmation of the diagnosis and classification of CP by a pediatric neurologist who used the diagnostic criteria for CP (Surveillance of Cerebral Palsy in Europe, 2000). Detailed visual assessment was performed and the results have been published including the Insight question inventory for PVD (Duke et al, 2020).…”
Section: Participantsmentioning
confidence: 99%